Causes and Effects of the Devaluation of the Values of the Modern Sport - Lukashchuk, Vitaliy (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The paper is devoted to theoretical analysis of the causes of devaluation of the values of modern sport. It is proved that a number of factors like politicization, ideologizing, commercialization and etc. lead to devaluation of values of modern sport. It is concluded that under the circumstances of mass culture trivialization of sport happens that transforms sport competition into entertainment. Bureaucracy also leads to transformation of values of modern sport. Bureaucratic control in sport leads to deepening alienation of sportsman from both the sports activity itself and the society in general. It is emphasized that the problem of overcoming of devaluation of values of modern sport can not be solved without changing of the relations in the society which should be first of all aimed at development of creative abilities of the personality, but not only the pragmatic interests.